SINTESIS N-3-CHLOROBENZOYLAMOXICILLIN DAN UJI AKTIVITAS ANTIBAKTERINYA TERHADAP Pseudomonas aeruginosa ATCC 27853 - Ika T. D. Kusumowati Siswandono; Marcellino Rudyanto (Universitas Muhammadiyah Malang, 2011)
N-3-chlorobenzoylamoxicillin were prepared by reacting 3-chlorobenzoylchloride with amine group of amoxicillin (acylation reaction). The reaction is nucleophilic substitution reaction in which primary amine group of the amoxicillin, which was nucleophilic in nature, attack C=O groups of benzoyl chloride-derivatives which has positive charge. The results showed that percentages of N-3-chlorobenzoylamoxicillin were 75%, respectively. Rf value of the resulting compounds different from Rf value of the amoxicillin. The structures were identified by Infra Red Spectrophotometry and Nuclear Magnetic Resonance (1H-NMR) Spectrometry. The results of the spectral analysis showed that spectra of amoxicillin and N-3-chlorobenzoylamoxicillin had changed significantly. The resulting structure was well fitted to the expected compounds. Antibacterial activities of N-3-chlorobenzoylamoxicillin against Pseudomonas aeruginosa ATCC 27853 were tested using dilution method. Minimum Inhibition Concentration achieved in the research represented the lowest level that can inhibit bacterial growth adequately. Analysis of the Minimum Inhibition Concentration on Pseudomonas aeruginosa ATCC 27853 showed significant differences between amoxicillin and N-3-chlorobenzoylamoxicillin.